Genome sequence of the cheese-starter strain Lactobacillus delbrueckii subsp. lactis CRL 581 - Hebert, Elvira Maria (2013)
We report the genome sequence of Lactobacillus delbrueckii subsp. lactis CRL 581 (1,911,137 bp, GC 49.7%), a proteolytic strain isolated from a homemade Argentinian hard cheese which has a key role in bacterial nutrition and releases bioactive healthbeneficial peptides from milk proteins.